(untitled) (PerCursos, 2006)
O presente artigo traz considerações relacionadas com o lugar que o professor ocupa no contexto atual da sociedade brasileira contemporânea e as implicações da auto-estima no desempenho docente e, um convite à retomada da caminhada, com foco no resgate do desejo de Ser Professor. Palavras-chave: Auto-estima. Professores. Desempenho Profissional. Abstract: This article analyzes the place that the teacher occupies in the current contemporary context of Brazilian society and the implications of self-esteem on the performance of the teacher. It is an invitation to travel a route once again, focusing on the recovery of the desire to be a teacher. Keywords: Esteems. Teachers. Professional performanc.